IDENTIFICATION OF SPECIFIC CEPHALOMETRIC MARKS IN PATIENTS WITH LATERAL CONDYLAR POSITION TEMPOROMANDIBULAR JOINT (World Science, 2020)
Relevance. Temporomandibular joint dysfunction is one of the most widely spread and common disease nowadays. It includes disorders on different levels of whole body and multi symptom as clinical manifestation. There is still less of evidence in ethiopathology of Temporomandibular dysfunction(TMD).Objective. The research aimed to find new etiological factors impacting the formation of TMJ, recorded growth and developmental disorders of the facial skull in the experimental group. Materials and methods. The sample group consisted of 59 patients. The experimental group included 38 patients with lateral joint displacement; the control group included 21 patients. Subjects were examined with functional probes, occlusion diagnosis with articulation paper Baush 200,100,8 microns, cephalometryc analysis by Grummons, computed tomography of temporomandibular joint, licensed software application Planmeca Romexis Viewer, statistical analyses with program IBM SPSS Statistic Base v.22.Results. 91.6% of patients with dentofacial deformities of the maxilla (ddm) also have TMJ with lateral displacement of the articular heads of the mandible. Patients without maxillary dentofacial deformities experience lateral displacement of the articular heads with a frequency of 8.7% and probable risk of 10.5 (95% CI 2.79-39.8). Patients in 1group (63,16%) experiences asymmetric inclination of the angles of the right and left upper jaw and occlusal plane around tooth number 6 and 7, 79.94% of patients in the experimental group recorded a displacement of the mandible